ChemInform Abstract: Rare‐Earth Cadmium Tellurite Chlorides with a Structural Type Exhibiting [Ln12(TeO3)12] Slabs Alternating with CdCl6 Octahedral Layers. Issue 34 (26th August 2014) - Kharitonov, Ivan D.; Charkin, Dmitri O.; Berdonosov, Peter S.; Black, Cameron; Downie, Lewis J.; Lightfoot, Philip; Dolgikh, Valery A.
Abstract The new compounds CdSm2(TeO3)2Cl4 (I), CdEu2(TeO3)2Cl4 (II), and CdGd2(TeO3)2Cl4 (III) are synthesized by the salt flux method from mixtures of LnOCl (Ln: Sm, Eu, Gd), TeO2, and CdCl2 (850 °C, 7 d).